HUMAN PARVOVIRUS B19 (HPVB19) IgG AND IgM LEVELS IN THE PATIENTS WITH RHEUMATOID ARTHRITIS - Ayhan Kamanlı; İlkkan Çalaşyer and Arzu Kaya (Archives of Rheumatology, 2001)
Rheumatoid arthritis (RA) is a chronic multisystem disease with an unknown etiology. In this study, Human Parvovirus B19 (HPV B19) IgG and IgM antibodies were determined in 29 RA, 16 Reactive arthritis (ReA) patients and 32 healthy subjects with Enzyme Linked Immunosorbent Assay (ELISA). Anti-HPV B19 IgG antibodies were positive in 89.7 % of patients with RA, in 87.5 % of patients with ReA and in 71.9 % of control group. Anti-HPV B19 IgM antibodies were positive in 20.7 % of patients with RA and 6.3 % of healthy control group. There was no HPV B19 IgM positivity in patients with ReA. Consequently, there were no statistically significant differences between patients with RA and control groups with respect to HPV B19 IgG and IgM antibodies.